TINJAUAN CSR BANK MANDIRI DALAM WIRAUSAHA MUDA MANDIRI (WMM) - Destrya Ajeng Larayaty, (2023)
This study analyzes the 2022 Independent Young Entrepreneur Program (WMM) as one form Corporate Social Responsibility (CSR) Bank Mandiri in encouraging economic growth to reduce unemployment by creating jobs, especially for the younger generation. The purpose of this research is to describe how event the 2022 Independent Young Entrepreneur program in Jakarta as one form Corporate Social Responsibility (CSR) Bank Mandiri. The research method used in this research is descriptive data analysis technique method in qualitative research based on primary data. As for the steps taken in this study, data collection was obtained from the process of interview data results, documentation then ended with conclusions. The results of the research show that there is a relationship with the program Corporate Social Responsibility (CSR) with the orientation of Independent Young Entrepreneurs or towards business people. Found that the program Corporate Social Responsibility (CSR) also has a positive impact in increasing entrepreneurial interest.